2016
DOI: 10.1007/s00606-016-1293-7
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus europaeus sp. nov., a widely distributed soil-borne species related to A. wentii (section Cremei)

Abstract: A new species belonging to Aspergillus section Cremei is described, A. europaeus sp. nov. This species is most closely related to A. wentii, A. dimorphicus, and A. chrysellus and can be distinguished by an unique phenotype (colour of sporulation, production of yellow soluble pigment on MEA, shape of vesicle, ornamentation of conidia), specific spectrum of produced exometabolites and internal transcribed spacers (ITS), b-tubulin and calmodulin gene sequence data. In total, 18 isolates were identified which orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…In these studies, from a total of 173 isolates belonging to the sections Aspergillus, Circumdati, Cremei, Flavipedes, Nidulantes, Terrei, Usti and Versicolores, we have identified 38 species, many of them considered cryptic because of their morphological similarity with the most common pathogens of each section studied. It is noteworthy that eight of these species were reported for the first time from animal and human clinical specimens, including three new ones, A. microperforatus, 12 A. pseudosclerotiorum, 16 In the present study, we identified A. europaeus of the section Cremei and although their isolation from clinical samples is rare, Hubka et al 29 suggested that A. europaeus is a relative common species in clinical settings and it has been overlooked and frequently misidentified, especially as A. wentii, the most well-known species of this section. The two species can be distinguished by the production of yellow soluble pigment on MEA in A. europaeus, which is not present in A. wentii.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…In these studies, from a total of 173 isolates belonging to the sections Aspergillus, Circumdati, Cremei, Flavipedes, Nidulantes, Terrei, Usti and Versicolores, we have identified 38 species, many of them considered cryptic because of their morphological similarity with the most common pathogens of each section studied. It is noteworthy that eight of these species were reported for the first time from animal and human clinical specimens, including three new ones, A. microperforatus, 12 A. pseudosclerotiorum, 16 In the present study, we identified A. europaeus of the section Cremei and although their isolation from clinical samples is rare, Hubka et al 29 suggested that A. europaeus is a relative common species in clinical settings and it has been overlooked and frequently misidentified, especially as A. wentii, the most well-known species of this section. The two species can be distinguished by the production of yellow soluble pigment on MEA in A. europaeus, which is not present in A. wentii.…”
Section: Discussionmentioning
confidence: 54%
“…In the present study, we identified A. europaeus of the section Cremei and although their isolation from clinical samples is rare, Hubka et al suggested that A. europaeus is a relative common species in clinical settings and it has been overlooked and frequently misidentified, especially as A. wentii , the most well‐known species of this section. The two species can be distinguished by the production of yellow soluble pigment on MEA in A. europaeus , which is not present in A. wentii . Moreover, they can be differentiated by the size of the conidial heads at the colony centre, which usually does not exceed 200 μm diam in A. europaeus , and are larger in A. wentii (approximately 500 μm diam) .…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations